PENGARUH PRODUK, PROMOSI, HARGA DAN SALURAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK MS GLOW DARI PERSFEKTIF EKONOMI ISLAM - Rahmad Iinminardi; Anzu Elvia Zahara; Nurrahma Sari Putri (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. This research aims to find out whether product quality, promotion, price and distribution channels influence the decision to purchase MS Glow products from the official MS Glow Tebo reseller. This research variable uses a dependent variable and an independent variable. The dependent variable of this research is the consumer's product purchasing decision. The independent variables are the influence of product, promotion, price and distribution channels. Research was conducted on consumers of the official MS Glow reseller, Tebo Regency, Jambi. The population in this study were consumers who purchased MS Glow Tebo products, Jambi. The sampling technique used purposive sampling and a research sample of 58 respondents was obtained. The method used is a quantitative method. This research uses instrument tests (validity and reliability tests), multicollinearity tests, normality tests, F tests and T tests. Meanwhile, data processing uses the SPSS program.Based on research results, product quality, promotion and price have a significant influence on the decision to purchase MS Glow products from the Official Reseller MS Glow Tebo. Meanwhile, distribution channel variables do not have a significant effect on purchasing decisions for MS Glow products at the Official Reseller MS Glow Tebo. This is proven based on the results of the t test and f test.